Preliminary Nutrient Determination and Regeneration of Pancreatic Islet Cells by Extracts of Spondias mombin Leaves in Streptozotocin-Induced Diabetic Rats - Nkeiruka Eluehike (Hamadan University of Medical Sciences, 2020)
Background: There is a growing trend towards the use of medicinal plant that can prevent degeneration of pancreatic cells and regenerate islet cells in diabetes treatment.